Retrogradna konstrukcija podobe gibanja prebivalstva na Slovenskem pred 18. stoletjem - Makarovič, Gorazd (Etnolog. Nova vrsta (Ljubljana), 2003)
Based on development demographic samples from territories with similar social and historical circumstances, an image is is constructed of the population trends in the territory of present-day Slovenia from the 7th to the 18th century: the article provides estimates on the total population and the number of adult women who participated in creating goods, historical conditions and events.
Keywords: demografija; demography; prebivalstvo; zgodovinski pregledi; rast prebivalstva; Slovenia; Slovenija; 7/18.st